DETOUR POLYNOMIALS OF COG-COMPLETE BIPARTITE GRAPH - AHMED, HAVEEN J.; ALI, AHMED M.; SALEH, GASHAW A. MOHAMMED (Journal of Duhok University, 2023)
The detour distance is a topological concept of graph theory, denoted by  and defined as the length of a longest  – path in a connected graph , where the vertices  and   belonged to the vertex set . In this paper, we find the detour polynomial, detour index for cog-complete-bipartite graphs, also, some special cases were taken for cog-complete bipartite graph to show the gear so that we can determine detour polynomial and detour index for any order